MR Assessment of Lumbar Disk Herniation Treated with Oxygen-Ozone Diskolysis: The Role of DWI and Related ADC versus Intervertebral Disk Volumetric Analysis for Detecting Treatment Response. Issue 3 (1st June 2013) - Splendiani, A.; Perri, M.; Conchiglia, A.; Fasano, F.; Di Egidio, G.; Masciocchi, C.; Gallucci, M.
We prospectively assessed the diagnostic criteria of morphologic MRI study (MMS) and the accuracy of DWI and related ADC values (DWI-ADC) versus intervertebral disk volumetric analysis (IDVA) for predicting shrinkage of lumbar disk herniation treated with oxygen-ozone (O2 -O3 ) diskolysis. Sixty-eight patients (36 men and 32 women; mean age 39) with lumbosciatica underwent O2 -O3 diskolysis. The six-month MRI follow-up was performed with FSE-T2 and T2-fat, SE-T1 and DWI-weighted images. IDVA was determined using OsiriX®. Diagnostic criteria and accuracy were evaluated with regards to DWI and related ADC in detecting response to ozone therapy. Fifty-eight of 68 patients had successful outcomes (responders), whereas ten patients showed unsatisfactory outcomes (non-responders). MMS showed that a centrally located herniated disk and grade 1 nerve root compression were more common in the responder group (p < 0.05). DWI-ADC and IDVA showed statistically significant shrinkage in the sixth month of follow-up (p < 0.05) with a mean ADC value reduction of 2.10 × 10 −3 mm 2 /s +/− 0.19 SD in the second month of follow-up (p < 0.05). DWI-ADC had an accuracy of 0.81 in detecting response to therapy around the second month of follow-up. DWI-ADC appear to be useful adjuncts to MMS in the follow-up of patients undergoing O2 -O3 diskolysis.